Visualization of the Reaction Trajectory and Transition State in a Hydrolytic Reaction Catalyzed by a Metalloenzyme. Issue 20 (23rd March 2017) - Selleck, Christopher; Clayton, Daniel; Gahan, Lawrence R.; Mitić, Nataša; McGeary, Ross P.; Pedroso, Marcelo Monteiro; Guddat, Luke W.; Schenk, Gerhard
Abstract: Metallohydrolases are a vast family of enzymes that play crucial roles in numerous metabolic pathways. Several members have emerged as targets for chemotherapeutics. Knowledge about their reaction mechanisms and associated transition states greatly aids the design of potent and highly specific drug leads. By using a high‐resolution crystal structure, we have probed the trajectory of the reaction catalyzed by purple acid phosphatase, an enzyme essential for the integrity of bone structure. In particular, the transition state is visualized, thus providing detailed structural information that may be exploited in the design of specific inhibitors for the development of new anti‐osteoporotic chemotherapeutics. Abstract : Magic trajectory : A high‐resolution structure of a purple acid phosphatase (PAP) showed two binding modes for a substrate mimic. Their overlay provided unprecedented insight into the structure of the transition state of the reaction catalyzed by this enzyme (see scheme).